The Montpellier Statement. Climate-Smart Agriculture: Towards Sustainable Landscapes and Food Systems. - Centre de coopération internationale en recherche agronomique pour le développement (2015)
Agriculture is a sector particularly vulnerable to climate change, which impacts livelihoods, especially that of the world’s poorest people. This places increased strain on global food systems, more than ever since expectations for meeting demand for food will change tremendously within the next 40 years. Agriculture has also a central role in strongly reducing greenhouse gas emissions and lies therefore at the heart of complex challenges to be addressed. Climate-Smart Agriculture (CSA) invites researchers, practitioners and policy makers to explore solutions combining three pillars, food security, climate change adaptation and mitigation, underpinning sustainable landscapes and food systems. This is essential since the sector is facing unprecedented uncertainty and risks. More than 600 researchers and 150 stakeholders and policy makers from 75 countries and 5 continents convened at the 3rd Global Science Conference on CSA in Montpellier, France, 16-18 March 2015. This shows that CSA is now a framework that mobilizes synergies and can lead to innovative and comprehensive solutions at local, regional and global levels. Delegates also confirmed that CSA solutions exist and can be brought into reality provided favorable policies and conditions.